Development of Elaeis guineensis/polyvinyl alcohol/carbon nanotube composites for efficient adsorption of dye: Experimental and theoretical approach - Zulfiqar, M. (Springer Science and Business Media Deutschland GmbH, 2021)
Industrial sectors are main responsible for continually releasing of harmful compounds in the form of wastewater. The potential utilization of bio-waste materials has received great attention to minimize the serious environmental issues. Therefore, the present research is focused to develop an Elaeis guineensis/polyvinyl alcohol/carbon nanotube (EG/PVA/CNT) composite via a simple polymerization method and tested to remove the dye from aqueous solutions. Field emission scanning electron microscopy (FE-SEM) and Fourier transform infrared spectroscopy (FTIR) characterizations were selected to confirm the morphology and chemical structures of composites. The water content measurement and swelling characteristics of EG/PVA/CNT were also elaborated. The evaluation of composites was explored through the elimination of methylene blue (MB) in a batch adsorption scheme including EG loading, pH of MB aqueous solutions, contact time, initial concentration of MB solutions, adsorbent dose and solution temperature. The results revealed that EG-based adsorbents have superior adsorption efficiency of 92.44. The adsorption kinetics was well explained by pseudo-second-order model, while in adsorption isotherms, Langmuir model was appropriate to demonstrate the MB adsorption data giving superlative removal aptitudes. The thermodynamic results revealed that adsorption onto EG/PVA/CNT was favorable, spontaneous and exothermic in nature, while activation energy informed the physical type of adsorption process. The adsorption mechanism of MB onto EG/PVA/CNT was also proposed. Moreover, EG/PVA/CNT was in stable form with good adsorption capacity and could easily be recycled. Based upon the present research, a strong strategy between EG, CNT and PVA could successfully develop an economical adsorbent for the treatment of different effluents. Â© 2021, Islamic Azad University (IAU).